Lower-Limb Power and 40-Meter Sprint Performance in Elementary Physical Education - Moch. Chandra Mukti; Fauzan Effendy; Dicky Oktora Mudzakir (SAKAGURU: Journal of Pedagogy and Creative Teacher, 2026)
Sprint performance in elementary physical education is a fundamental motor skill that requires lower-limb force production, coordination, acceleration ability, and efficient movement technique. This study aimed to examine the relationship between leg muscle power and 40-meter sprint performance among Grade V elementary school students. A quantitative correlational design was employed involving 17 students from UPTD SDN 1 Singakerta, Krangkeng District, Indramayu Regency, Indonesia. Leg muscle power was measured using a vertical jump test, while sprint performance was assessed through a 40-meter sprint test recorded in seconds. The data were analyzed using descriptive statistics and simple linear regression at a significance level of .05. The results showed that students obtained a mean vertical jump score of 78.53 cm (SD = 7.80) and a mean 40-meter sprint time of 14.24 seconds (SD = 2.31). The regression analysis revealed a statistically significant relationship between vertical jump performance and 40-meter sprint time, F (1,15) = 6.740, p = 0.020, with a moderate correlation coefficient (R = 0.557) and an explained variance of 31.0% (R² = 0.310). Since sprint performance was measured as completion time, the finding indicates that students with higher leg muscle power tended to complete the 40-meter sprint in a shorter time. This study concludes that leg muscle power is a meaningful physical component of short-distance running performance among elementary school students, although sprint ability remains influenced by other factors such as technique, coordination, maturation, and motivation. The implication is that physical education teachers should integrate safe, progressive, and age-appropriate lower-limb power activities with sprint technique instruction to support evidence-informed motor development in elementary physical education.